Preparation method of P34HB / CNC-PVAc air filtering film
Through the preparation method of P34HB/CNC-PVAc air filter film, the problem of insufficient mechanical properties and thermal stability of the existing air filter film under high pressure or high temperature conditions is solved, and a more efficient and environmentally friendly air filtration effect is achieved.
Patent Information
- Application Number
- CN202510021950.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-04
AI Technical Summary
When used under high pressure or high temperature conditions, the mechanical properties and thermal stability are insufficient, making it difficult to effectively capture fine particulate matter and harmful gases, and there is a problem of secondary pollution of the environment after use.
Using the preparation method of P34HB/CNC-PVAc air filter film, an air filter film with improved spinning liquid performance, improved mechanical strength and thermal stability was prepared by dissolving P34HB powder in a solvent, adding CNC-PVAc, stirring evenly, and electrospinning was performed.
It improves the mechanical strength and thermal stability of the air filter film, enhances the filtration efficiency and electrostatic adsorption capacity of tiny particles, reduces the impact on the environment, and achieves a more efficient and environmentally friendly air filtration effect.
Smart Images

Figure CN119746655A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and specifically relates to a method for preparing a P34HB / CNC-PVAc air filtration film, which can be used in the field of air filtration. Background Art
[0002] With the increasing severity of air pollution and the improvement of environmental protection requirements, the performance requirements for filter membranes are also constantly increasing. Traditional non-woven filter membranes cannot capture fine particles or harmful gases, and there are problems such as secondary pollution of the environment after use, which cannot meet people's requirements for efficient and environmentally friendly filter membranes.
[0003] P34HB is a specific type of polyhydroxyalkanoate (PHA) that is biocompatible and biodegradable. It can be safely disposed of after use as a filter membrane, reducing the impact on the environment. Compared with filter membranes prepared from traditional polymers, the fibers spun from pure P34HB solutions have large diameters, low mechanical strength and thermal stability, which limits the use of filter membranes under high pressure or high temperature conditions.
[0004] Chinese patent CN102906123A grafts polylactic acid (PLA) onto nanocrystalline cellulose (NCC) and blends it with PLA or PHA and PHB to prepare a nanocomposite with stronger mechanical properties than pure PLA. Chinese patent CN116672904A discloses a high-porosity polylactic acid high-efficiency air filtration membrane based on triboelectric effect and its preparation method, and uses left-handed polylactic acid as raw material to prepare a triboelectric principle air filtration membrane.
[0005] At present, the research on air filtration membranes has the problem of single material properties, high porosity and air filtration efficiency, but poor mechanical properties and thermal stability; the application scenarios of nanocomposite materials with good mechanical properties are limited to specific fields such as biomedicine, and the performance in air filtration related properties is unsatisfactory. Therefore, it is urgent to modify the PHA spinning solution to obtain higher performance air filtration membranes. Summary of the invention
[0006] In order to improve the problems of uneven fiber diameter, poor mechanical properties and low thermal stability of existing air filtration membranes, the present invention provides a method for preparing a P34HB / CNC-PVAc air filtration membrane, which comprises the following steps in sequence:
[0007] (1) After dissolving P34HB powder in a solvent, CNC-PVAc is added thereto, and the mixture is stirred evenly to prepare a P34HB / CNC-PVAc electrospinning solution containing CNC-PVAc;
[0008] (2) Applying voltage at both ends to perform electrostatic spinning, collecting the deposited spun fibers, and producing an air filtration membrane.
[0009] Furthermore, the amount of CNC-PVAc added is 1%-10% of the mass of P34HB, and most preferably 10%.
[0010] Furthermore, the solvent is DCM.
[0011] Furthermore, the uniform stirring condition in (1) is stirring at 30-50°C for 6-12 hours, and most preferably stirring at 40°C for 8 hours.
[0012] Furthermore, the voltage applied at both ends is a positive voltage of 15 kV and a negative voltage of -5 kV.
[0013] Furthermore, the feed rate, working temperature and relative humidity during electrospinning were 0.05 mL / min, 30±2° C. and 55±5%, respectively.
[0014] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0015] 1. DCM can dissolve P34HB well. The introduction of CNC-PVAc not only improves the performance of the spinning solution, but also improves the mechanical strength and thermal stability of the filtration membrane.
[0016] 2. The introduction of CNC-PVAc improves the filtration efficiency of tiny particles (such as PM0.3).
[0017] 3. The introduction of CNC-PVAc enhances the electrostatic adsorption capacity of the filter membrane for particulate matter, further improving the filtration performance.
[0018] 4. The addition of CNC-PVAc is beneficial to promote biodegradation to a certain extent. After completing the filtration task, the prepared air filtration membrane can return to nature harmlessly through the biodegradation process, reducing the impact on the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The figure shows the change in mechanical strength of the air filtration membrane as the amount of CNC-PAVc added in Comparative Example 1 increases.
[0020] Figure 2 As the amount of CNC-PAVc added in Comparative Example 2 increases, the filtration efficiency and pressure drop of PM0.3 change at different gas volume flow rates (10 / 32 / 65 / 85 L / min).
[0021] Figure 3As the amount of CNC-PAVc added in Comparative Example 2 increases, the quality factor of PM0.3 changes at different gas volume flow rates (10 / 32 / 65 / 85 L / min).
[0022] Figure 4 The dielectric constant change of the air filtration membrane after adding different contents of CNC-PAVc in Experimental Example 1.
[0023] Figure 5 This is the mass loss diagram of P34HB and its composite fiber film as the amount of CNC-PAVc added in Experimental Example 2 increases. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0025] The CNC-PVAc used in the following examples was prepared according to the method disclosed in the following literature: Hao Wu, Xiangdong Hua, Jian Hu, Xueping Liu, Jianming Zhang, Fabrication of stereocomplex-type poly(lactic acid) nanocomposites based on the selective nucleation of poly(vinyl acetate) modified cellulose nanocrystals[J], Carbohydrate Polymers Volume 347, 1 January 2025, 122716).
[0026] Example 1
[0027] A method for preparing a P34HB / CNC-PVAc air filtration membrane, comprising the following steps:
[0028] (1) After dissolving P34HB powder in dichloromethane (DCM), CNC-PVAc was added thereto and stirred at 40°C for 8 h to prepare P34HB / CNC-PVAc solutions containing 0 wt%, 1 wt%, 5 wt%, and 10 wt% CNC-PVAc, respectively (all referring to the mass ratio of CNC-PVAc to P34HB), i.e., uniform electrospinning solutions, in which the ratio of P34HB to solvent dichloromethane was 100 g / L.
[0029] (2) The electrospinning solution was electrospun using electrospinning technology: the electrospinning solution was transferred to a 10 mL plastic syringe with a 20# metal needle. In order to facilitate the removal of the fiber film, a layer of tin foil was wrapped on the outside of the collector. During the spinning process, a positive voltage of 15 kV and a negative voltage of -5 kV were applied. The feed rate, working temperature and relative humidity were 0.05 mL / min, 30 ± 2 °C and 55 ± 5%, respectively. A stainless steel grounded roller with a rotation speed of 120 r / min was used to collect the deposited spun fibers. The distance between the spinneret and the collector was 18 cm. The spun fiber film was placed in an oven at 60 °C. After evaporating the excess solvent, composite fiber films containing different concentrations of CNC-PVAc were prepared, which were named P34HB, P34HB-1%, P34HB-5%, and P34HB-10%, respectively.
[0030] Comparative Example 1
[0031] This comparative example investigates the effect of the introduction of CNC-PVAc on the mechanical strength and thermal stability of the filtration membrane
[0032] Air filter membrane mechanical properties test: Mechanical properties First, use a standard cutter to cut the air filter membrane into pieces, cut into 115mm×6mm dumbbell-shaped specimens, then randomly select three points in the specimen working area to measure with a thickness gauge, and take the average value of the three points as the thickness of the specimen. During the experiment, the upward tensile rate of the universal tensile machine was set to 20mm·min -1 , each spline was tested 5 times and the average value was taken.
[0033] The tensile strength and Young's modulus of each sample were tested to evaluate the comprehensive mechanical properties of the sample. Figure 1 As shown. From the tensile strength obtained, it is obvious that the addition of different contents (1wt%, 5wt% and 10wt%) of CNC-PVAc significantly enhanced the mechanical properties of the air filtration membrane. The tensile strength of P34HB-10% is 2.61MPa, which is 1.50 times that of the pure P34HB electrospun membrane (1.73MPa). At the same time, the Young's modulus of the P34HB-10% air filtration membrane is 2.08 times that of pure P34HB, which may be due to the good interface interaction between the P34HB matrix and CNC-PVAc, which effectively transfers the load to the CNC-PVAc filler particles, thereby achieving multiple enhancements.
[0034] The thermal stability of the filter membrane is one of its performance requirements, especially when used in sterilization or high temperature environments. The filter membrane needs to be able to withstand a certain temperature without losing its filtration efficiency or physical structure. This experiment used the TGA method to study the effect of CNC-PVAc content on the thermal stability of air filtration membranes under a nitrogen atmosphere. From the test results, it was found that the temperature of the pure P34HB fiber membrane when it lost 5wt% was 232.37℃. After adding CNC-PVAc, the maximum temperature of the P34HB-10% fiber membrane when it lost 5wt% was 240.42℃, an increase of 8.05℃. The thermal stability of the air filtration membrane was improved, ensuring the filtration efficiency and safety stability of the composite filter membrane during use.
[0035] Comparative Example 2
[0036] This comparative example explores the effect of the introduction of CNC-PVAc on the filtration effect of the filtration membrane by comparing the filtration efficiency at four volume flow rates.
[0037] Air filtration test characterization: The PM filtration performance of the filter membrane was evaluated by an air filtration test system. ATM 221, NaCl aerosol generator produced by TOPAS in Germany was used to release particles (0-12.5μm). Four air flow rates of 10L / min, 32L / min, 65L / min and 85L / min were set for the experiment. AFC131 was used to record the aerosol concentration and obtain the filtration efficiency of particles of different particle sizes.
[0038] Four volume flow rates (10 L / min, 32 L / min, 65 L / min, 85 L / min) were used to evaluate the filtration efficiency of the air filter membrane for PM 0.3. The results are shown in Figure 2 As shown. Obviously, for fine particles, especially ultrafine particles 0.3μm, a proper sacrificial pressure drop can achieve a higher filtration efficiency. With the increase of volume flow, the pressure drop of the fiber film gradually increases. When the high-velocity gas passes through, it will cause resistance to gas flow, generate turbulence and eddy currents. On the other hand, the number of gas molecules in the film pores increases, and more gas molecules collide with the pore wall, increasing friction resistance and thus leading to an increase in pressure drop.
[0039] from Figure 2It can be seen that compared with the P34HB-10% composite fiber membrane with certain self-generating performance, it still maintains a relatively high filtration efficiency at 32L / min, and the filtration efficiency of PM 0.3 is 93.28%. This is partly because the average fiber diameter of P34HB-10% is slightly smaller than that of pure P34HB, among which the diameter of P34HB-1% membrane is the smallest, but the filtration efficiency of PM 0.3 at 32L / min is only 85.39%, slightly lower than the filtration efficiency of P34HB-10% at 32L / min; therefore, in addition to the diameter, there is another important reason to consider, because under low airflow capacity, the membrane carries a certain charge after vibration and friction with the air, and the fine particles in the air are easily captured by the highly polarized membrane with high surface potential and high dielectric constant, which also proves that the addition of CNC-PVAc not only increases the physical interception filtration mechanism but also increases the effect of electrostatic action on filtration.
[0040] Smaller fiber size leads to greater pressure drop, while the interception efficiency and inertial impaction efficiency increase, thus compensating for the increase in pressure drop. The capture efficiency of suspended particles in the air. The overall filtration performance of the membrane filtration film is usually determined by the quality factor (QF) value. When the air flow rate gradually increases, the QF value of all filtration membranes drops sharply due to the increase in pressure drop. Each membrane reaches its maximum value at low air flow rates. Figure 3 It can be seen that the P34HB-10% fiber membrane shows a relatively high QF value (0.0725Pa -1 , 10L / min), while the QF of pure P34HB membrane is only (0.0592Pa -1 , 10L / min). Therefore, the filtration membrane modified by CNC-PVAc showed excellent comprehensive filtration performance compared with the original P34HB membrane due to the self-charging function triggered by airflow vibration. It was confirmed that the addition of CNC-PVAc had a comprehensive improvement on the P34HB electrospun membrane from fiber morphology to filtration mechanism.
[0041] Test Example 1
[0042] This test example tests the dielectric constant of the air filtration membrane obtained in Example 1 to explore the effect of the addition of CNC-PVAc on the electrostatic adsorption capacity of the filtration membrane for particulate matter and its effect on the filtration performance.
[0043] Test of dielectric constant of air filter membrane: Use dielectric impedance spectrometer to test the dielectric constant. Before the test, the sample is cut into discs with a circular cutter with an inner diameter of 25 mm, and a circular copper sheet with a diameter of 30 mm is used as an electrode to measure the dielectric constant of the air filter membrane under study in the frequency range of 10 0 Hz-10 6Dielectric constant (ε) in Hz.
[0044] Figure 4 The dielectric constant change of the air filtration membrane was shown, and it was found that the dielectric constant ε of the pure P34HB electrospun membrane decreased with the increase of frequency. In the high-frequency state, the energy absorbed by the dipole of P34HB is reduced, so the dipole is not oriented in the direction of the applied field, and the C=O and -CH3 of P34HB cannot rotate freely with the increase of the external electric field. Compared with the lowest dielectric constant (2.76) of the original P34HB film, the highest dielectric constant of the P34HB-10% air filtration membrane can reach 3.49. This is because CNC-PVAc contains abundant -OH polar groups, which have a large dipole moment, making it easier for molecules to form an ordered arrangement, and the dipole orientation is conducive to improving the dielectric constant. Since the increase in the dielectric constant of the material is conducive to increasing the surface charge accumulated during the contact process, it is conducive to enhancing the electrostatic adsorption of particulate matter by the filtration membrane.
[0045] Test Example 2
[0046] This test example studies the biodegradation process of P34HB / CNC-PVAc air filtration membrane and evaluates the effect of CNC-PVAc addition on the degradation behavior of air filtration membrane. Mass loss test: The electrospun membrane obtained in Example 1 was cut into small sheets of 2 cm × 2 cm and numbered 1, 2, 3, and 4 respectively. These numbered film samples were placed in the soil for biodegradation experiments. Before measuring the mass loss, the sample needs to be rinsed with distilled water several times to remove soil particles and other impurities that may be attached to the surface of the sample. After rinsing, use an appropriate method (such as filter paper blotting or in a constant temperature oven) to remove moisture from the surface of the sample. In this test example, the sample was vacuum dried at a temperature of 40°C to ensure that the moisture in the sample was completely removed. The weight loss rate of the sample was calculated using the following formula: Weight loss rate (%) = (W0-W1) W0 × 100%. Where W0 records the initial mass of the sample before degradation, and W1 is the mass of the sample after degradation.
[0047] Depend on Figure 5We can see that after 15 days of degradation, there was a small loss in the mass of P34HB and its composite fiber film, which indicates that the material has begun to undergo a biodegradation process. At 30 days, the mass loss effect was more obvious, with the highest mass loss rate reaching 37.28%, indicating that the degradation process accelerated over time. During the process from 15 to 30 days, the degradation rate increased. In addition, it can be found from the data that the addition of CNC-PVAc promotes the degradation of P34HB because the addition of CNC-PVAc introduces more -OH groups, enhances the hydrophilicity of the material, and is more sensitive to moisture during soil degradation, increasing the absorption of moisture, providing a suitable living environment for microorganisms, and accelerating the breakage of ester groups in the film.
[0048] The results show that the addition of CNC-PVAc is beneficial to promote biodegradation to a certain extent. After completing the filtration task, the air filtration membrane prepared in this study can return to nature harmlessly through the biodegradation process, reducing the impact on the environment. The use of this filter membrane not only helps promote the development of environmentally friendly filters, but also has important significance for achieving sustainability throughout the life cycle of products and materials.
[0049] In summary, it can be seen that the air filtration film prepared by the present invention has high filtration efficiency and low pressure drop due to the presence of surface charge on the fiber, and is easy to degrade, and is an environmentally friendly material. In addition, the film has flexibility and good triboelectric output performance. Therefore, by selecting a suitable triboelectric negative electrode material, the fiber film can convert the stimulus signal in the environment into a real-time signal, and prepare fully flexible electronic devices for use in the wearable field, which has broad application prospects.
Claims
1. A method for preparing a P34HB / CNC-PVAc air filtration membrane, comprising the following steps in sequence: (1) After dissolving P34HB powder in a solvent, CNC-PVAc is added thereto, and the mixture is stirred evenly to prepare a P34HB / CNC-PVAc electrospinning solution containing CNC-PVAc; (2) Applying voltage at both ends to perform electrostatic spinning, collecting the deposited spun fibers, and producing an air filtration membrane.
2. The preparation method according to claim 1, characterized in that: The amount of CNC-PVAc added accounts for 1%-10% of the mass of P34HB.
3. The preparation method according to claim 1, characterized in that: The solvent was DCM.
4. The preparation method according to claim 1, characterized in that: The stirring condition in (1) is to stir uniformly at 30-50°C for 6-12h.
5. The preparation method according to claim 1, characterized in that The voltage applied across the two ends is 15kV for positive voltage and -5kV for negative voltage.
6. The preparation method according to claim 5, characterized in that The feed rate, working temperature and relative humidity during electrospinning were 0.05 mL / min, 30±2° C. and 55±5%, respectively.
Citation Information
Patent Citations
Nanocomposite biomaterials of nanocrystalline cellulose (ncc) and polylactic acid (pla)
CN102906123A
High-porosity polylactic acid high-efficiency air filtering membrane based on triboelectric effect and preparation method thereof
CN116672904A